Gastrointestinal stromal tumour treated with neoadjuvant imatinib. Issue 7 (23rd June 2005) - Loughrey, M B; Mitchell, C; Mann, G B; Michael, M; Waring, P M
Abstract : This report describes a case of unresectable primary gastrointestinal stromal tumour (GIST) treated with imatinib on a neoadjuvant basis, before subsequent successful surgical resection. After six months of imatinib, computed tomography and positron emission tomography imaging demonstrated a significant size reduction and complete metabolic response to treatment, rendering the tumour resectable. Mutational analysis showed an activating KIT mutation in exon 11. The pathological appearance of the resected tumour was heterogeneous with extensive necrosis, cystic and myxoid change, extensive hypocellularity, and patchy foci of residual viable tumour. The implications for this management option of radiological, pathological, and molecular assessment are discussed.